PENGARUH PIJAT KAKI DAN RENDAM AIR HANGAT CAMPUR GARAM TERHADAP PENURUNAN EDEMA KAKI PADA IBU HAMIL TRIMESTER III DI PUSKESMAS BANGETAYU GENUK KOTA SEMARANG - Ayu Septiyana; Nella Vallen Ika Puspita; Mudy Oktiningrum (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of foot massage and soaking in warm water mixed with salt on reducing leg edema in third-trimester pregnant women. This type of research is Experimental design with the group Pre-Test and Post-test design approach model. The population in this study were all third-trimester pregnant women who experienced physiological leg edema at the Bangetayu Health Center, Genuk sub-district, Semarang City, totaling 32 people from June to July 2022. The sampling technique used a total sampling of 32 people. The data collection tools in this study were Standard Operating Procedures (SOP) for Foot Massage and Warm Water Soak mixed with salt, Observation Sheets, Questionnaires, and Metlin in Millimeter units. The results of the study obtained a Z value of 5.045 which means that every one time intervention of foot massage and soaking in warm water mixed with salt, which is given one time a day for five days, third-trimester pregnant women have the potential to be 5.045 times to be able to reduce the degree of edema. The Wilcoxon test results obtained a significance of ≤ 0.05, and it was found that there was an effect of foot massage and soaking in warm water mixed with salt on the reduction of leg edema in third-trimester pregnant women at the Bangetayu Health Center, Genuk District, Semarang City. Keywords: Foot edema, Foot massage, Soak using warm water mixed with salt